2005
DOI: 10.1016/s0917-2394(05)70045-8
|View full text |Cite
|
Sign up to set email alerts
|

A Study of dental caries prevalence in 12–14 year old school children in Ibadan, Nigeria

Abstract: The aim of the study was to determine dental caries prevalence among a representative sample of 12-14 year old school children in Ibadan, Nigeria with a view of determining Restorative Index and Met Need Index of the studied population. Dental caries was diagnosed according to the WHO method. Out of the 577 children in the age group, 65 children (11.2%) had dental caries experience as expressed with the DMFT index. More than 85% of the children were caries free. A mode of one DMFT was the highest score for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 5 publications
4
22
0
Order By: Relevance
“…Previous clinic based studies in Nigeria have shown that dental visits by children were symptomatic visits and pain from dental caries and its sequelae were the reasons for the visits 6,13,14) . A significantly higher number of female children visiting the dentist in this study is expected as an earlier study has reported a higher mean DMFT value in female children 15) . Various modifiable factors that influence regular dental visits have been identified.…”
Section: Discussionsupporting
confidence: 63%
“…Previous clinic based studies in Nigeria have shown that dental visits by children were symptomatic visits and pain from dental caries and its sequelae were the reasons for the visits 6,13,14) . A significantly higher number of female children visiting the dentist in this study is expected as an earlier study has reported a higher mean DMFT value in female children 15) . Various modifiable factors that influence regular dental visits have been identified.…”
Section: Discussionsupporting
confidence: 63%
“…Our results demonstrate that the children of the parents with good oral health also have better dental status (control group) than children whose parents are with poor dental health (examined groups). These results corroborate many other studies (9,10,11,12). Dental caries is the main reason for premature tooth loss and it is a behavioral disease.…”
Section: Resultssupporting
confidence: 94%
“…The DMFT for the 12‐ and 15‐ year‐olds was 0.7 and 1.2 respectively, with very low level of restorative care. The multiple regional studies in the country continue to show that the prevalence of dental caries in the permanent dentition remains high ranging from 13.9% in Ile‐Ife to 33.0% in Benin, 15.5% to 35.5% in Enugu, 5.7% to 30.8% in Lagos, and 11.2% in Ibadan (O. O. Sofola, M. O. Folayan, A. B. Oginni, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…The DMFT for the 12-and 15-year-olds was 0.7 and 1.2 respectively, with very low level of restorative care 6 . The multiple regional studies in the country continue to show that the prevalence of dental caries in the permanent dentition remains high ranging from 13.9% in Ile-Ife to 33.0% in Benin, 15.5% to 35.5% in Enugu, 5.7% to 30.8% in Lagos, and 11.2% in Ibadan [7][8][9][10][11][12][13][14][15][16] Oginni, personal communication). In the primary dentition, the prevalence ranges from 10.9% in Ile-Ife to 6.4% to 22.5% in Lagos 7,8,11,[15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%